2017
DOI: 10.1002/2017jd026501
|View full text |Cite
|
Sign up to set email alerts
|

New particle formation from sulfuric acid and amines: Comparison of monomethylamine, dimethylamine, and trimethylamine

Abstract: Amines are bases that originate from both anthropogenic and natural sources, and they are recognized as candidates to participate in atmospheric aerosol particle formation together with sulfuric acid. Monomethylamine, dimethylamine, and trimethylamine (MMA, DMA, and TMA, respectively) have been shown to enhance sulfuric acid‐driven particle formation more efficiently than ammonia, but both theory and laboratory experiments suggest that there are differences in their enhancing potentials. However, as quantitati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
158
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(166 citation statements)
references
References 57 publications
7
158
1
Order By: Relevance
“…Numerous lab experiments and quantum chemical calculations reported amines play an important role in atmospheric nucleation and the growth of new particles (Zhang et al, 2012;Jen et 5 al., 2014;Chen et al, 2015aChen et al, , b, 2017Olenius et al, 2017), and oxalic acid, one of the most abundant dicarboxylic acids, was also proposed to be involved in NPF, and to be more readily bound to methylamine than to ammonia (Guo et al, 2016;Arquero et al, 2017;Hong et al, 2018). So far, it has been a challenge to accurately measure the mass concentrations of aminiums and oxalate in nucleation mode particles (Bzdek et al, 2013;Tao et al, 2016).…”
Section: The Roles Of Amines and Oxalic Acid In Growing New Particlesmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous lab experiments and quantum chemical calculations reported amines play an important role in atmospheric nucleation and the growth of new particles (Zhang et al, 2012;Jen et 5 al., 2014;Chen et al, 2015aChen et al, , b, 2017Olenius et al, 2017), and oxalic acid, one of the most abundant dicarboxylic acids, was also proposed to be involved in NPF, and to be more readily bound to methylamine than to ammonia (Guo et al, 2016;Arquero et al, 2017;Hong et al, 2018). So far, it has been a challenge to accurately measure the mass concentrations of aminiums and oxalate in nucleation mode particles (Bzdek et al, 2013;Tao et al, 2016).…”
Section: The Roles Of Amines and Oxalic Acid In Growing New Particlesmentioning
confidence: 99%
“…NPF events induced by iodine species were frequently observed at coastal locations, e.g., most notably at Mace Head on the west coast of Ireland, in presence of enhanced biological emissions during low-tide, ocean upwelling or the sea-ice melting conditions (O'Dowd et al, 20 2002 a,b;Wen et al, 2006;O'Dowd and de Leeuw, 2007;Ehn et al, 2010;Huang et al, 2010;McFiggans, et al, 2010;Allan et al, 2015;Sellegri et al, 2016). Moreover, amines were reported to enhance H2SO4-H2O nucleation and promote the growth of newly formed particles (Ge et al, 2011;Zhang et al, 2012;Yu et al, 2016;Olenius et al, 2017). The observation in the eastern Pacific Ocean revealed that an increase in gaseous precursors of amines and DMS affected the particulate chemical composition and cloud properties (Sorooshian et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Low molecular weight amines are commonly found in the atmosphere in both gas and particle phases (Ge et al, 2011a, b). Based on present theoretical calculations (Kurtén et al, 2008;Loukonen et al, 2010;Paasonen et al, 2012;Olenius et al, 2017), laboratory simulations (Wang et al, 2010a, b;Kurtén et al, 2014;Erupe et al, 2011;Almeida et al, 2013;Yu et al, 2012) and field observations (Smith et al, 2010;Kürten et al, 2016;Tao et al, 2016), amines in the atmosphere have been proved to play an important role in new particle formation and subsequent particle growth and thus affect both the number concentrations of aerosols and cloud condensation nuclei that are closely relevant to regional climate (Tang et al, 2014;Yao et al, 2018). For example, dimethylamine (DMA) was found to be a key species involved in new particle formation events in the urban area of Shanghai, and the nucleation mechanism was likely to be H 2 SO 4 -DMA-H 2 O ternary nucleation .…”
mentioning
confidence: 99%
“…This effect could also have been caused by higher loadings of precursors that favored the new particle formation. These precursors, such as sulfuric acid, amines, and extremely low-volatility organic vapors, were reported to dominate the formation and initial growth of new particles (Paasonen et al, 2010;Ehn et al, 2014). In contrast, the different GRs between the marginal seas and the OUC could have been related to the availability of semi-volatile precursors, which promote the growth of larger new particles (Yao et al, 2010;Riipinen et al, 2012).…”
Section: Fr Gr Nminp and D Pgmax In Marine Atmospherementioning
confidence: 99%